Shamans and plant sacraments: maintaining indigenous traditions and identity in a globalized world - Stacy B. Schaefer (Universidad de Caldas, 2006)
Abstract: This paper examines the unique relationship shamans have with special psychoactive plants valued in their cultures. In particular the use of peyote (Lophophora williamsii) in Huichol Indian culture of Mexico, and coca (Erythroxylim coca) in the indigenous cultures of San Pedro de Atacama in Northern Chile, and Aymaras of the La Paz region of Bolivia will be discussed. The central role the shamans and these plants play in traditional beliefs and practices will be presented, as well as how these plants symbolize Indian identity in a time of globalization.